WOMEN’S SECONDARY EDUCATION IN THE NORTHERN CAUCASUS IN THE II HALF OF THE XIX - BEGINNING OF XX CENTURY - Olga I. Shafranova (Наука. Инновации. Технологии)
The article studies the problems of the history of women’s education. In the system of secondary female education of pre-revolutionary Russia was part of secondary schools - gymnasiums and eparchial female school. The article gives characteristics of the process of creation of women’s education and the evolution of female education in the North Caucasus.